2012
DOI: 10.1016/j.neuroscience.2011.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal expression analysis of the calcium-binding protein calumenin in the rodent brain

Abstract: Calumenin is a Ca2+-binding protein that belongs to the CREC superfamily. It contains six EF-hand domains that exhibit a low affinity for Ca2+ as well as an endoplasmic reticulum retention signal. Calumenin exhibits a broad and relatively high expression in various brain regions during development as demonstrated by in situ hybridization. Signal intensity of calumenin is highest during the early development and then declines over time to reach a relatively low expression in adult animals. Immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Another protein involved in signalling is Protein-tyrosine phosphatase-like A domain containing 1 protein (PTPLAD1), an integral membrane protein implicated in small GTPase mediated signal transduction and fatty acid biosynthetic process 76,77 . The third novel CLN3 IP, Calumenin (CALU), is a calcium binding protein that is highly expressed in various brain regions during development and functions in protein folding and sorting in the ER 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Another protein involved in signalling is Protein-tyrosine phosphatase-like A domain containing 1 protein (PTPLAD1), an integral membrane protein implicated in small GTPase mediated signal transduction and fatty acid biosynthetic process 76,77 . The third novel CLN3 IP, Calumenin (CALU), is a calcium binding protein that is highly expressed in various brain regions during development and functions in protein folding and sorting in the ER 78 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the protein expression level of CALU in embryonic and neonatal heart is higher than that in adult mouse heart (Sahoo et al., ). Similarly, the expression pattern of CALU protein is highest during the early stages of development in the brain and then declines with age to reach a relatively low expression in adult animals (Vasiljevic et al., ). (Lee, Kwon, & Kim, ) showed that apoptosis was significantly reduced by calumenin overexpression in endoplasmic reticulum stress‐induced cells.…”
Section: Discussionmentioning
confidence: 99%
“…In other animals, calumenin is a multifunctional Ca 2+ ‐binding protein involved in ER function, cell migration, and other functions (Zheng, Wang, Teng, & Chen, ). In addition, in the mouse brain, neural progenitors specifically express Calu , which might have roles in the migration and differentiation of neurons (Vasiljevic et al., ). Consistently, during planarian regeneration, Djcalu was specifically expressed in differentiating cells, which would be migrating (Figure c,d).…”
Section: Discussionmentioning
confidence: 99%